IBM KELOMPOK TERNAK UNGGAS DI KECAMATAN MANUJU KABUPATEN GOWA PROPINSI SULAWESI SELATAN - Purwanti, Sri; Agustina, Laily; Asriany, Anie; Jamilah, Jamilah (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
The target of this devotion activity is the group of poultry breeder Baji Minasa and Cahaya Po'rong in ManujuSubdistrict Gowa regency of South Sulawesi. The productivity of livestock in this group has not been good or is still said tobe low. Bran ammonia by utilizing  feces and bran around as high protein source as well as an herbal medicine for ducksand domestic chickens as feed additive and composting. After that proceed with the socialization of activity programs onmembers of livestock groups. The execution phase is carried out by counseling on the importance of providing and makingfeeds independently by utilizing local resources and the importance of sanitation or bio-security in village management. Themethod used is PRA (Participatory Rural Appraisal)/RRA (Rapid Rural Appraisal). Methods of approach to solvingproblems, including counseling, training and visits, field school education (SL), and learning by doing. Through this activit yfarmers and agricultural extension, workers are expected to synergize to learn to utilize the available local resources intonutrient-rich feed by self-production thereby reducing the cost of raising livestock. The results obtained by tabulating thegiven questionnaire indicate that the breeder does not recognize alternative feed sources of high protein and wantscontinuous counseling, given the knowledge of breeders and the introduction of technology is still lacking. Overall the resul tsobtained are very positive responses as well as the active participation of members of livestock groups